The Quit India Movement in Bombay Karnataka: Role of Undivided Dharwad District - Bharateshagouda S. Shiriyappagoudar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The Quit India Movement was a Movement launched at the Bombay Session of the All India Committee by Mahatma Gandhi on 8th August 1942, during Second World War, demanding an end to British Rule in India. After Britain failed to secure Indian support for the British War effort with the Cripps Mission, M K Gandhi made a call to “Do or Die” in his Quit India Movement on 8th August 1942 at the Gowaliya Tank Maidan.(Ground) Viceroy Lithlithgow described the movement as “by the most serious rebellion since 1857” The Quit India Movement in Bombay Karnataka (Now Kitturu Karnataka) was marked by widespread protest, attacks on Government property like post offices and railway stations and the formation of a parallel government in Dharwad and Belagavi Districts. Initiated on in August the Movement was a direct result of the failure of the Cripps Mission and future the “Do or Die” decision given by Mahatma Gandhi in Bombay. The local response included the destruction of Government property, and despite harsh British suppression, the Movement showcased immense local commitment to achieving Independence.